Evaluation of nutrient expert - a decision support tool through SSNM in soybean: EVALUATION OF NUTRIENT EXPERT - A DECISION SUPPORT TOOL THROUGH SSNM IN SOYBEAN - C M KHANDA; ANSHUMAN NAYAK; S K MOHANTY; B S NAYAK; SUBHASHREE DAS; N MANDI (Journal of Oilseeds Research, 2020)
A field experiment was carried out during kharif seasons of 2017-18 and 2018-19 in AICRP on Soybean at Regional Research and Technology Transfer Station of OUAT, Bhawanipatna, Kalahandi, Odisha to evaluate the effectiveness ofsite specific nutrient management(SSNM)in soybean usingNutrient Expert, a decision support tool. Seven treatments comprising of T1: SSNM(NE) (25:23:19 kg N:P2O5 :K2O/ha), T2: T1-N omission (0:23:19 kg N:P2O5:K2O/ha), T3: T1-P omission (25:0:19 kg N:P2O5:K2O/ha), T4: T1-K omission (25:23:0 kg N:P2O5:K2O/ha), T5: RDF (25:100:50:50kg N:P2O5 :K2O:S /ha), T6: Farmers practice (20:20:20 kg N:P2O5 :K2O/ha) and T7: Absolute control (No fertilizer) were tried in randomized block design (RBD) with three replications. Recommended dose of fertilizer (25:100:50:50 kg N:P2O5 :K2O:S/ha) recorded maximum seed yield ofsoybean (1465 kg/ha) which was at par with application of fertilizer based on site specific nutrient management [SSNM (NE) 25:23:19 kg N:P2O5:K2O/ha] with seed yield of 1352 kg/ha. Yield data from the omission plot treatments suggested that N is the most important major nutrient for enhancing the seed yield of soybean followed by P and K. There was 28.1% reduction in seed yield when N was omitted from SSNM (NE). Omission of nitrogen, phosphorus and potassium application from SSNM (NE) recorded 33.7, 25.1 and 21.7% reduction in seed yield, respectively, as compared to application ofNPKS (RDF). Application ofRDF earned higher gross return to an extent of 8% and 28% over SSNM (NE) and Farmers Practice, respectively, whereas, net return (`13271/ha) and return/rupee invested (1.49) were higher in SSNM (NE).